The Development of Non-Enzymatic Glucose Biosensors Based on Electrochemically Prepared Polypyrrole–Chitosan–Titanium Dioxide Nanocomposite Films - Al-Mokaram, A.M.A.A.A.; Yahya, R.; Abdi, M.M.; Mahmud, H.N.M.E. (MDPI, 2017)
The performance of a modified electrode of nanocomposite films consisting of polypyrrole-chitosan-titanium dioxide (Ppy-CS-TiO2) has been explored for the developing a non-enzymatic glucose biosensors. The synergy effect of TiO2 nanoparticles (NPs) and conducting polymer on the current responses of the electrode resulted in greater sensitivity. The incorporation of TiO2 NPs in the nanocomposite films was confirmed by X-ray photoelectron spectroscopy (XPS) spectra. FE-SEM and HR-TEM provided more evidence for the presence of TiO2 in the Ppy-CS structure. Glucose biosensing properties were determined by amperommetry and cyclic voltammetry (CV). The interfacial properties of nanocomposite electrodes were studied by electrochemical impedance spectroscopy (EIS). The developed biosensors showed good sensitivity over a linear range of 1-14 mM with a detection limit of 614 M for glucose. The modified electrode with Ppy-CS nanocomposite also exhibited good selectivity and long-term stability with no interference effect. The Ppy-CS-TiO2 nanocomposites films presented high electron transfer kinetics. This work shows the role of nanomaterials in electrochemical biosensors and describes the process of their homogeneous distribution in composite films by a one-step electrochemical process, where all components are taken in a single solution in the electrochemical cell.